The effectiveness of Rutin for prevention of surgical induced endometriosis development in a rat model - Hatef Talebi (Nature Portfolio, 2021)
Abstract Apoptosis and antioxidant mechanisms are pathways for the treatment of endometriosis (Endo). Rutin (Rtn) is an antioxidant flavonol that induces apoptosis. This study, for first time, was conducted to evaluate the effects of rutin on Endo through apoptosis and antioxidant mechanisms. The experimental Endo was induced in 24 rats and then the animals were subdivided into Endo-sole, 3000 and 6000 µg/kg rutin (Rtn-3000 and Rtn-6000) and vitamin C groups. After 4 weeks, the expression of Bcl2, Bax, anti Pro Caspase-9, cleaved Caspase-9, pro PARP, pro Cleaved PARP, Pro PARP, pro mTOR and mTOR were assessed by western blotting technique. The protein concentrations of malondialdehyde (MDA), total antioxidant capacity, and super oxide dismutase and gutathione peroxidase were also evaluated. TUNEL staining was also used for the detection of apoptosis. Caspase-9 and concentration of antioxidants were higher in the treated groups compared to Endo-sole group (P < 0.05). The results also showed that rutin decreased the expression of Bcl2 and MDA concentration (P < 0.05). The results for TUNEL staining showed that the animals treated with Rtn-6000 and vitamin C showed higher apoptosis. Rutin induces apoptosis by the expression of Bcl-2, Bax and caspase and also antioxidant activity by increasing antioxidants concentrations.